La tregua - Benedetti, Mario, 1920-2009. ([Santiago de Chile] : eBooks Patagonia, 2011)
Santomé, a 50 year old "depressed" retiring office worker, struggles with his free time, a young lover, 3 rebeloius children, and a stressing daily office routine.
Online resource; title from ePub and PDF title page (Digitalia, viewed June 26, 2014)
Keywords: Uruguay -- Social life and customs -- Fiction; Electronic books